MyNote: Multiplatform Reactive Integration System with The Clean Architecture Development Concept - Arrijal Amar Ma'ruf; Dedi Gunawan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2023)
The application needs in the current digital era are very broad and varied. In its development, these applications undergo a transformation, thus demanding application developers to create applications that suit their devices. This study applies the concept of the reactive paradigm which is implemented into a multiplatform application system and the concept of clean architecture in the process of creating a simple note management application